Cadaver preservation for display in malaysian anatomy museums: methods, challenges, and cultural considerations - Abas, Razif (Universiti Putra Malaysia Press, 2025)
The preservation of cadaveric specimens in anatomy museums is a cornerstone of medical education and research. This review examines the unique practices of cadaver preservation in Malaysian anatomy museums, addressing the following research question: What are the current methods, challenges, and cultural considerations in cadaver preservation in Malaysian anatomy museums? The review provides a detailed exploration of locally developed preservation methods, ethical and cultural influences, and a comparative analysis of traditional and modern techniques, such as formalin-based embalming and plastination. Furthermore, it evaluates the sustainability and future trends in cadaver preservation, ensuring these museums continue to serve as educational resources for future generations.